Cognitive Control in Suicide Ideators and Suicide Attempters - Brokke, Silje Støle; Landrø, Nils Inge; Haaland, Vegard Øksendal (Frontiers in Psychology, 2020)
There is a need to understand more of the risk factors involved in the process from suicide ideation to suicide attempt, as we know suicide attempt to be the most predictive risk factor for subsequent suicide. Cognitive control processes may be important factors in assessing vulnerability to suicide. A version of the Stroop procedure, D-KEFS Color-Word Interference Test and Behavior Rating Inventory of Executive Function (BRIEF-A) were used in this study to test the cognitive inhibition and cognitive shift, as well as to assess everyday executive function, of 98 acute suicidal psychiatric patients. The Columbia Suicide History form was used to identify the group of suicide ideators and suicide attempters. Results showed that suicide attempters scored lower on cognitive inhibition than suicide ideators who had no history of attempted suicide. The self-report in the BRIEF-A inventory did not reflect any cognitive differences between suicide ideators and suicide attempters. A logistic regression analysis showed that a higher inhibition score was associated with the suicide ideation group, whereas a higher cognitive shift score was associated with the suicide attempt group. The results found in this study suggest that suicide attempters may not struggle with cognitive flexibility but may struggle to withhold a response. We need to understand more of how different cognitive control functions work together when it comes to suicidal vulnerability.